Contextual Teaching and Learning Method in Studying Arabic - Muhammad Ilham Muchtar (State Institute of Islamic Studies (IAIN) Palu, 2017)
The concept of Contextual Teaching and Learning teaching emphasizes the full student's activity both physically and mentally. Contextual Teaching and Learning considers that learning is not a memorizing activity, considering facts, demonstrating repetitious exercise but a process of experience in life in nature . Contextual Teaching and Learning in learning Arabic is able to improve students' learning achievement in learning Arabic because learners are increasingly eager to learn or have the confidence to know something that is not yet known so as to make learners is not depressed in teaching and learning process.